The Effect of Preparatory Posture on Goalkeeper's Diving Save Performance in Football - Ibrahim, Rony; Kingma, Idsart; de Boode, Vosse; Faber, Gert S.; van Dieën, Jaap H. (Frontiers in Sports and Active Living, 2019)
Identifying the optimal preparatory posture of football goalkeepers can be very relevant for improving goalkeepers' diving save performance, and coaching practices of technical and strength and conditioning coaches. This study aimed to analyse the effect of different starting stance widths and knee flexion angles on movement time, center of mass (CoM) trajectory and velocity in goalkeepers' diving saves. Ten elite goalkeepers performed dives from preferred (PT) and imposed postures, by altering knee angle (45, 75, and 90°) and stance width (50, 75, and 100% of leg length) independently, at the starting position. Repeated measures ANOVA showed a main effect of preparatory posture on dive time (p < 0.01). Pairwise comparisons showed that the fastest dive movement time was observed when goalkeepers started from a stance width of 75% (SW75). CoM traveled a larger distance between contralateral and ipsilateral peak ground reaction forces in SW75 than PT (p < 0.05). The goalkeepers were also more efficient in SW75, as a smaller countermovement and vertical velocity range were observed during high and low dives, respectively, from SW75 than PT (p < 0.05). Thus, diving from a position with wider stance width than the preferred one leads to shorter movement time, and a faster and more direct CoM trajectory toward the ball.